APLIKASI MARCOV CHAIN DALAM PENENTUAN PERULANGAN LITOLOGI PADA KALI WIDORO KECAMATAN PATUK DAN SEKITARNYA, KABUPATEN GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - rizqi, al hussein flowers; Elkawi Hawinu, Nodyka (Institut Teknologi Nasional Yogyakarta, 2024)
Geostatistics is a branch of statistics that focuses on the analysis and interpretation of spatial data in earth science. Marcov chain is one of the most frequently used methods of geostatistics where this method can analyze and predict secular processes in space and time. In geology, the marcov chain method is widely used to model vertical and lateral variations in stratigraphic sequences. The research area is located in Patuk District, Gunungkidul Regency, Special Region of Yogyakarta or at coordinates S -878815 and E 110.548088. The research location is included in the Sambipitu formation, according to previous research the Sambipitu formation consists of sandstone alternating with tuffan sandstone which contains many trace fossils. The results of the marcov chain analysis showed that the highest value was found in the lithological loops of sandstones which showed that it was likely that the lithological loops would be formed in the form of sandstones and the results of the chi-squared analysis showed that the lithology in the research area was not patterned and the H1 hypothesis was rejected and H0 was accepted